A Corpus-Based Investigation of Extra-Textual, Connective, and Emphasizing Additions in English-Chinese Conference Interpreting - Li, Ruitian; Cheung, Andrew K. F.; Liu, Kanglong (Frontiers in Psychology, 2022)
Findings from conference interpreting research in the Chinese context have suggested that interpreters barely produce extra-textual additions in rigidly structured press conferences, and that adding connectives and intensifiers is only required to help the English-speaking audience capture the logic embedded in implicit Chinese interclausal relations. Previous research in the Chinese context has tended to draw data almost exclusively from the Chinese Premier’s Press Conference interpreting, which features interpreting from Chinese into English. In order to enrich conference interpreting corpora in Asia and to examine additions in the opposite interpreting direction for the same language pair, this study drew on authentic materials of six interpreted press conferences held at the American Institute in Taiwan (AIT). Contrary to previous research, our results showed that conference interpreters exhibited a certain degree of “visibility” through producing extra-textual additions, which is typical of interpreting in various community-based settings. Moreover, the addition of extra connectives and intensifiers that are common in Chinese-to-English interpreting was also identified. It is proposed that the interpreters’ production of extra-textual additions is connected with the specific context of the AIT, whereas the connective and emphasizing additions are to a large extent caused by the grammaticalization process wherein particular linguistic devices change into discourse markers to fulfill the communicative needs in both English and Chinese.